An investigation into the relative adhesion of Candida dubliniensis and Candida albicans to human cells and extracellular matrix proteins - Jordan, Rachael P. C. (Trinity College (Dublin, Ireland). School of Dental Science, 2009)
Candida dubliniensis is a germ tube-positive, chlamydospore-producing yeast species originally recovered from the oral cavities of HIV-infected individuals and AIDS patients and first described in 1995. It is closely related to Candida albicans. Despite their close phenotypic, genotypic and phylogenetic relationship, epidemiological and infection model data indicate that C. dubliniensis is significantly less pathogenic than C. albicans. As adherence to host cells and tissue is an essential early step in the establishment of disease, the comparative ability of C. dubliniensis and C. albicans to adhere to human buccal epithelial cells (BECs), monolayers of the TR146 human epithelial cell line and extracellular matrix (ECM) proteins was investigated in order to obtain insights into the differential pathogenicity of the two species. The role of the agglutinin-like sequence {ALS) genes in the adhesion of both species to BECs was also investigated.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin